2018
DOI: 10.1039/c7tc05355j
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic printing directing photonic crystal bead 2D code patterns

Abstract: We developed a new microfluidic printing technology for the fabrication of multi-signal 2D code patterns with structural colors and fluorescence properties, which may have potential applications in anti-counterfeiting and optoelectronic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Thus, the multidipole system reproducibly arranges itself to reach an electrostatic equilibrium, keeping the energy of the system at the minimum level. Future study of this effect is warranted (including the potential influence of electrohydrodynamic flow), but we propose that the self‐assembly of beads into symmetric patterns may someday be useful for making photonic crystals or plasmonic structures …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the multidipole system reproducibly arranges itself to reach an electrostatic equilibrium, keeping the energy of the system at the minimum level. Future study of this effect is warranted (including the potential influence of electrohydrodynamic flow), but we propose that the self‐assembly of beads into symmetric patterns may someday be useful for making photonic crystals or plasmonic structures …”
Section: Resultsmentioning
confidence: 99%
“…Chen and co‐workers demonstrated a fluorescent 2D photonic crystal code pattern by microfluidic printing technology using polymeric core‐quantum dots shell spheres. [ 152 ] The micropattern of the 2D code inscribed bright green and red structural colors at different pixels and exhibited a fluorescent image under UV excitation as shown in Figure 19b. The polarization feature of chiral nematic CNCs could modulate the fluorescence in an anisotropic way, leading to polarization‐dependent structural color‐luminescence encryption.…”
Section: Strategies For Anticounterfeiting Via Structural Colorsmentioning
confidence: 99%
“…Reproduced with permission. [ 152 ] Copyright 2018, The Royal Society of Chemistry. c) Showcasing the potential of CNCs films for polarization‐based encryption.…”
Section: Strategies For Anticounterfeiting Via Structural Colorsmentioning
confidence: 99%
“…265 Chen et al showed a letter-shaped magnetic-responsive panel display based on magnetic-optic dual-functional Janus supraballs and a microfluidic strategy. 21,267,268,271,272 The researchers fabricated hydrophobic poly(tert-butyl acrylate) (PtBA) PCs via a facile soap-free emulsion polymerization. They demonstrated enhanced photoluminescence intensity of the CdSe@ZnS quantum dot film in the LCD device based on the unique photonic bandgap of PtBA PCs.…”
Section: Displaysmentioning
confidence: 99%